Venture capital exit pressure and venture exit: A board perspective - Yao, Ting; O'Neill, Hugh (Strategic Management Journal, 2022)
Abstract Research Summary Venture capital funds have a limited lifecycle. As the fund ages, venture capitalists (VCs) are motivated to promote venture exit discussions with the venture board. We investigate the impact of VCs' exit pressure on the hazard of four types of venture exit (IPO, high‐value M&A, low‐value M&A, and liquidation), considering how VCs' exit pressure influences board collaboration. We find that while the VCs' exit pressure does not affect the hazard of IPOs, the pressure significantly increases the hazard of M&A and liquidation. Achieving important milestones does not reduce the impact of exit pressure on the hazard of low‐value M&A and liquidation. Independent directors moderate the impact of the VC's exit pressure, increasing the hazard of high‐value M&A and lessening the hazard of liquidation. Managerial Summary We investigate whether VCs' exit pressure due to an approaching deadline for fund liquidation influences the time to venture exit and how board composition affects the relationship between VCs' exit pressure and venture exit. Data from a sample of 219 VC‐backed U.S. surgical device ventures founded during 1989–2014 suggest that VCs' exit pressure decreases the time to M&A (both high‐value and low‐value M&A) and liquidation. Boards with more independent directors facilitate high‐value M&A and delay liquidation. VCs' exit pressure does not affect the time to IPO. These results provide evidence of the impact of the venture capital fund's finite life on investees other than the VCs and confirm the crucial role of independent directors in managing VCs' exit pressure.